A pilot split‐scalp study of combined fractional radiofrequency microneedling and 5% topical minoxidil in treating male pattern hair loss. (1st October 2018) - Yu, A.‐J.; Luo, Y.‐J.; Xu, X.‐G.; Bao, L.‐L.; Tian, T.; Li, Z.‐X.; Dong, Y.‐X.; Li, Y.‐H.
Summary: Background: Various trials have been conducted on the management of male pattern hair loss (MPHL), but the outcomes often seem to be limited. Adjuvant therapies are urgently needed. Aim: To evaluate the efficacy and safety of combined fractional radiofrequency microneedling (FRM) and 5% topical minoxidil in the treatment of male pattern hair loss. Methods: In total, 19 Chinese men were enrolled in this randomized, controlled, split‐scalp trial. Participants received monotherapy with 5% topical minoxidil twice daily to one half of the scalp, while on the other half of the scalp the treatment with twice‐daily 5% topical minoxidil was combined with five sessions of FRM at 4‐week intervals. Mean hair count and hair thickness, global assessment by the investigators, subject self‐assessment and adverse effects were assessed. Results: After 5 months of treatment, mean hair count increased from 44.12 ± 21.58 to 73.14 ± 25.45 on the combined‐therapy side and from 46.22 ± 18.77 to 63.21 ± 19.22 on the monotherapy side, while mean hair thickness increased from 53 ± 13 μm to 71 ± 15 μm and from 52 ± 16 μm to 66 ± 14 μm, respectively. Compared with the monotherapy side, the combined‐therapy side had a higher degree of improvement in both hair count ( P = 0.01) and hair thickness ( P = 0.02). Conclusions: Combined treatment with fractional radiofrequency microneedle and 5% topical minoxidil could be an effective and safe treatment option for male pattern hair loss.